NILAI LOKALITAS ORANG BAJO DALAM CERPEN “LANDO” (Locality Value of Bajonese in “Lando” Short Story) - Heksa Biopsi Puji Hastuti (Kandai, 2012)
Short story entitled “Lando” written by Ucu Agustin tells the story about two kids  who  live  far  away  from  their  ancestor‟s hometown.  The  author  raisedlocality of Bajonese as the color of her short story. This paper discusses  localityvalue of Bajonese conteined therein. The approach used in the discussion is structuralism with reference to Francois-Robert Zacot‟s ethnographic research result at the phase of understanding locality value in the story. From the discussion it is known that the author explores the nuances of bajo by using dictions from Bajo language. The value of Bajonese locality is represented with the inclusion of Bajo culture either in the form of myths and beliefs and way of Bajo people life that cannot be separated from sea. Even readers who have not learned at all about bajo can acquire imagery of Bajonese by reading “Lando” short story. Cerpen “Lando” karya Ucu Agustin berkisah tentang dua anak Bajo yang hidup jauh dari kampung halaman leluhur mereka. Pengarang mengangkat nuansa lokal orang Bajo sebagai warna untuk cerpennya. Tulisan ini membahas tentang nilai lokalitas orang Bajo yang termuat di dalamnya. Pendekatan yang digunakan ialah pendekatan struktural dengan mengacu pada hasil penelitian etnografi Francois-Robert Zacot pada tahap pemahaman nilai lokalitas orang Bajo   dalam   cerpen   ini.   Dari   pembahasan   diketahui   bahwa   pengarang mengeksplorasi  nuansa  Bajo  dengan  penggunaan  beberapa  kosa  kata  daribahasa    Bajo.    Nilai    lokalitas    orang    Bajo    direpresentasikan    dengandimasukkannya budaya Bajo baik berupa mitos dan kepercayaan maupun cara hidup mereka yang tidak lepas dari laut. Pembaca yang belum mengetahui samasekali  tentang  orang  Bajo,  bisa  memperoleh  gambaran  yang  cukup  denganmembaca cerpen “Lando”.